2005
DOI: 10.1002/ajmg.a.31020
|View full text |Cite
|
Sign up to set email alerts
|

Isolated 6q terminal deletions: An emerging new syndrome

Abstract: Deletions of the distal part of the 6q chromosome have not been associated with a clearly distinctive and recognizable phenotype. In order to determine if a "6q terminal deletion syndrome" could be delineated, we compared the phenotype of two new cases with those patients reported in literature presenting with a similar deletion. Cases with more complex karyotypes were excluded. The deletion in our patients was accurately analyzed by loss of heterozygosity (LOH) and fluorescence in situ hybridization (FISH) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 17 publications
(23 reference statements)
2
52
1
Order By: Relevance
“…Our patients displayed only mild joint laxity (which is likely related to hypotonia rather than to a connective tissue abnormality). Both had 6q27 deletions smaller than the one detected in the patient of Mosca et al [2010] (5.65 Mb); however deletion size also in this case is apparently unrelated to the presence of EDS-like features since the two patients published by Bertini et al [2006] and three out of five patients of Striano et al [2006] had deletions larger than 6 Mb but apparently lacked features of EDS.…”
contrasting
confidence: 54%
“…Our patients displayed only mild joint laxity (which is likely related to hypotonia rather than to a connective tissue abnormality). Both had 6q27 deletions smaller than the one detected in the patient of Mosca et al [2010] (5.65 Mb); however deletion size also in this case is apparently unrelated to the presence of EDS-like features since the two patients published by Bertini et al [2006] and three out of five patients of Striano et al [2006] had deletions larger than 6 Mb but apparently lacked features of EDS.…”
contrasting
confidence: 54%
“…[1][2][3][4][5][6][7][8][9]15,16 Though the clinical phenotypes associated with this deletion are quite variable, reports in unrelated subjects from independent investigators have shown that ACC, PNH, polymicrogyria, hydrocephalus, and cerebellar malformations are the consistently observed features. A recent analysis of a comprehensive map of loci for ACC from 374 patients revealed that chromosome 6q27 was one of the few loci wherein six or more subjects with ACC have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Structural brain malformations are consistently observed in these patients and include agenesis of the corpus callosum (ACC), periventricular nodular heterotopia (PNH), polymicrogyria, hydrocephalus, and cerebellar malformations. [1][2][3][4][5][6][7][8][9][10] Whereas previous studies have attempted to delineate the critical region responsible for brain malformations in patients with terminal 6q27 deletions, the sensitivity of the methodologies used has prevented the fine-mapping of the critical region. 1,6 A detailed genomic analysis of the subtelomeric chromosome 6q region would help identify the putative genes involved in the causation of brain malformations.…”
Section: Introductionmentioning
confidence: 99%
“…Very significant dysmorphic characteristics are present in most chromosamal disorders associated with epilepsy (3). We presented a 7-year old male patient who was referred to our clinic because of resistant epilepsy and whose chromosomal analysis on peripheral blood revealed mos 47,XY,+r (6)[3]/ 46,XY, r (6)[40]/ 45,XY,-6 [7]. Based on this case we aimed to discuss the significance of use of cytogenetic techniques and multidiciplinary study in understanding clinical and basic mechanisms of epilepsy.…”
Section: To the Editormentioning
confidence: 99%
“…Afterwards, cases from different areas have been reported occasionally. These diseases reported have generally been diagnosed postnatally, but there are also patients who have been diagnosed prenatally (3,4,5,6). Chilren with ring chromosome 6 who have been reported until the present time in the literature have been observed to display a wide clinical spectrum ranging from normal intelligence level to neurologic and dysmorphic findings including epilepsy, hydrocephaly, microcephaly and mental retardation (5,6).…”
Section: To the Editormentioning
confidence: 99%